Penanaman nilai empati melalui aplikasi “Teman Disabilitas” di SD islamic leader school - Amanda Aulia Rahmatika; Syarip Hidayat; Muhammad Rijal Wahid Muharram (IKIP Siliwangi, 2023)
This research is a research on the development of the â€œTeman Disabilitasâ€ application to instill the value of empathy for people with physical disabilities. The purpose of the research is to find out the need for applications based on the value of empathy for disability in elementary schools, develop and describe the form of application designs based on the value of empathy for disabilities in elementary schools, conduct trials of application products based on empathy values for disabilities in elementary schools, and produce a form of the end of the application product based on the value of empathy for disabilities in elementary schools. The method in this research is Design Based Research according to Reeves. This research was conducted at SD Islamic Leader School. The stages in this research are (1) principles and collaborative problem and practice analysis, (2) prototype development as a solution based on existing design, and technological innovations, (3) iterative testing cycle and solution refinement in practice, and (4) cycle improvement and refinement of solutions in practice. The types of data collection used are interviews, questionnaires, observations, and Values Clarification Test. The final product of this research is the â€œTeman Disabilitasâ€ application. This research trial was conducted before and before using the â€œTeman Disabilitasâ€ application using the Values Clarification Test. Based on data analysis, there was an increase in the empathy value of students before and before using the